2015
DOI: 10.3390/sports4010001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Video-Based Visual Training on Decision-Making and Reactive Agility in Adolescent Football Players

Abstract: This study investigated the trainability of decision-making and reactive agility via video-based visual training in young athletes. Thirty-four members of a national football academy (age: 14.4 ± 0.1 years) were randomly assigned to a training (VIS; n = 18) or a control group (CON; n = 16). In addition to the football training, the VIS completed a video-based visual training twice a week over a period of six weeks during the competition phase. Using the temporal occlusion technique, the players were instructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…Further studies should experiment with the effects of using field-based training compared to video-based training. In this context, Young and Rogers [18] demonstrated a significant improvement (31%) in decision making time following 11 sessions of SSGs in Australian football players [37]. The authors of the latter investigation concluded that cognitive skills could be enhanced via specific agility training.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies should experiment with the effects of using field-based training compared to video-based training. In this context, Young and Rogers [18] demonstrated a significant improvement (31%) in decision making time following 11 sessions of SSGs in Australian football players [37]. The authors of the latter investigation concluded that cognitive skills could be enhanced via specific agility training.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the method of analysing video where the team's responsibilities are mapped as an adaptive demand generated by a tactical soccer game. Described by (Nimmerichter, Weber, Wirth and Haller, 2016) that football players can improve perceptual-cognitive skills with a 6 min video-based training performed twice a week. Interpret by (Bruland, Hagemann, and Strau, 2005) to initiate quick actions, athletes must focus their attention and visual perception on the most relevant information sources or key events.…”
Section: Discussionmentioning
confidence: 99%
“…In the study about female volleyball players, Aktas (2015), determined that there was a relationship between female volleyball players' agility performance and perception, decision-making parameters, the number of correct responses (DT accurate number), accurate response time (DT time), speed distance estimation (HMT), binary processing ability and viewing angle values, but there was no statistically significant relationship between visual perception (TAVTMB) and reasoning (SPM) values. Nimmerichter et al (2016) found in their study conducted about eighteen young male footballers that their performance of reactive agility developed after 6 weeks of video-based training and there was a a significant relationship between the reaction speed. Young and Willey (2010) determined in their study about 31 male football players that there was a significant relationship between the total time of the reactive agility test and the response time to the stimulus.…”
Section: Journal Of Education and Learningmentioning
confidence: 97%